STUDENTS MOTIVATION AND PREFERENCE TOWARD ON-LINE LEARNING - Qurinta Shinta (Bajang Institute, 2022)
The purpose of this descriptive qualitative study is to examine students'motivation toward on-line learning and their preference on of this type of learning. The target population consisted of 81 USM students from Faculty of Communication Science who took English TOEFL course. Questionnaires were distributed to the students during the learning process. The questionnaire consists of 10 objective questions with 5 answer choices: strongly agree, agree, quite agree, disagree, strongly disagree and 2 free answer questions. The total score of the questionnares was 2902 indicating that students’ motivation was on moderate category which is in line with the result of similar research. While most students prefer on-line learning due to its practicality to access the streaming, material, submitting assignments; others find that they lack of concentration, interaction, and ability to master the subject and external problem like unstable wifi connection.